Conversion of Carbon Dioxide into Chemical Vapor Deposited Graphene with Controllable Number of Layers via Hydrogen Plasma Pre-Treatment - Yotsarayuth Seekaew; Nantikan Tammanoon; Adisorn Tuantranont; Tanom Lomas; Anurat Wisitsoraat; Chatchawal Wongchoosuk (Membranes, 2022)
In this work, we report the conversion of carbon dioxide (CO2) gas into graphene on copper foil by using a thermal chemical vapor deposition (CVD) method assisted by hydrogen (H2) plasma pre-treatment. The synthesized graphene has been characterized by Raman spectroscopy, X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The results show the controllable number of layers (two to six layers) of high-quality graphene by adjusting H2 plasma pre-treatment powers (100–400 W). The number of layers is reduced with increasing H2 plasma pre-treatment powers due to the direct modification of metal catalyst surfaces. Bilayer graphene can be well grown with H2 plasma pre-treatment powers of 400 W while few-layer graphene has been successfully formed under H2 plasma pre-treatment powers ranging from 100 to 300 W. The formation mechanism is highlighted.